Proximate Analysis and Mineral Composition of the Lord's Apple Cinnamon Tea - Oscar Notoriuwa Aghedo; Osagie Ferdinand Amayo; Clinton Aiyevbekpen (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study examines the proximate and mineral composition of Lord's Apple Cinnamon Tea, a functional beverage with health benefits from apple and cinnamon bioactive compounds. Apples contain flavonoids like quercetin, which reduce oxidative stress and improve lipid metabolism, while cinnamon provides cinnamaldehyde, which enhances insulin sensitivity and lowers blood glucose. The study aimed to assess the tea's nutritional profile through proximate and mineral analysis. The methodology involved the collection and preparation of tea samples, followed by mineral analysis using Flame Atomic Absorption Spectrophotometry (FAAS) and proximate analysis to determine moisture, ash, fiber, lipids, and protein content. The results showed high levels of potassium (191,496.7 mg/kg), sodium (28,997.67 mg/kg), and iron (7,500.01 mg/kg), along with trace elements like copper, zinc, magnesium, and manganese. Proximate analysis revealed fiber (68.92%), moisture (23.04%), ash (10.48%), lipids (8.48%), and protein (8.1%). These findings suggest the tea may support cardiovascular health, digestion, and antioxidant activity. It is recommended as part of a healthy diet, with further research needed to explore its long-term effects.